Misi Gereja dalam Menghadapi Realitas Budaya di Indonesia: Refleksi Markus 16:15 - Ayub Rusmanto; Aji Suseno (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2021)
This paper discusses contemporary missions related to church planting as part of the implementation of the command of the Lord Jesus in Mark 16:15, “Go into all the world and preach the gospel to all creatures”, which is implemented by planting churches in the reality of contemporary Indonesian culture. The method used in writing this paper is a descriptive qualitative method with a literature approach, the author will describe descriptively the basis of Christian mission and the urgency to review or update the construction and implementation of missions in the reality of contemporary Indonesian culture. If investigating the church's mission is urgent to respond to the Great Commission in preaching the Gospel to the formed Congregation. The results of this paper conclude that the implementation of the church's mission must pay attention to the cultural realities in Indonesia today. Because the mission of the church without paying attention to the context of the recipient will find complications and even failures in carrying out the Great Commission. In this case, an understanding and policy of cultural reality in Indonesia today is needed in accordance with the current context in which the church is present.Tulisan ini mempercakapkan mengenai misi masa kini bersinggungan dengan penanaman gereja sebagai bagian dari implementasi perintah Tuhan Yesus dalam Markus 16:15, “Pergilah ke seluruh dunia, beritakanlah Injil kepada segala makhluk”, yang diimplementasikan penanaman gereja dalam realitas budaya Indonesia masa kini. Metode yang digunakan dalam penulisaa karya tulis ini adalah metode kualitatif deskriptif dengan pendekatan kepustakaan, penulis akan menguraikan secara deskriptif tentang landasan misi Kristen dan urgensinya melakukan kajian ulang atau meng-up date terhadap kontruksi dan implementasi misi dalam realitas budaya Indonesia masa kini. Jika menginvitigasi misi gereja merupakan urgensi meresponi Amanat Agung dalam pemberitaan Injil kepada Jemaat yang terbentuk. Hasil penulisan ini disimpulkan dalam implementasi misi gereja harus memperhatikan realitas budaya di Indonesia masa kini. Sebab misi gereja tanpa memperhatikan konteks penerima akan mendapati kerumitan bahkan kegagalan dalam menjalankan Amanat Agung.  Dalam hal ini diperlukan pemhaman dan kebijakan realitas budaya di Indonesia masa kini sesuai dengan konteks kekinian di mana gereja hadir